Covenant Violation as A Pathway For Interpreting The Gospel: An Engagement With Schilder and The Yoruba Thought - Oluwabukunmi Popoola; Tony Salurante (Jurnal Jaffray, 2023)
This paper discussed Schilder's position on the theology of covenant in engagement with the Yoruba thought, identifying their points of agreement and departure and establishing the fruitfulness of Schilder's thoughts on the theology of covenant among the Yorubas. Through library and field studies, it answered whether the levity accorded the Christian faith in the recent by the Yoruba people group is not unconnected to a shallow understanding of the implications of breaking the covenant relationship entailed in the Christian faith. And how the implications of covenant violation, as discussed by Klaas Schilder, can be fruitful for the Yoruba people's understanding of the covenant of grace.